2013
DOI: 10.1002/pts.2044
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes of Extra Virgin Olive Oil Packaged in Coloured Polyethylene Terephthalate Bottles Stored Under Different Lighting Conditions

Abstract: In this paper, the influence of light storage and the exposure on quality parameters of a monovarietal extra virgin olive oil packaged in polyethylene terephthalate (PET) bottles were investigated. Coloured PET bottles (clear, green, orange, white and blue) were stored under different artificial lighting conditions in order to simulate the market environment (one fluorescent cool white lamp) and to perform an accelerated test (four fluorescent cool white lamps); storage in the dark was considered as a control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Extra‐virgin olive oil (EVOO) is obtained from olives solely by mechanical or other physical processes. The presence of natural antioxidant components such as carotenoids, chlorophylls, and tocopherol is a typical characteristic of EVOO, which is an advantage in comparison with other vegetable oils that have these components removed because of the refining process they are submitted (Rizzo, Torri, Licciardello, Piergiovanni, & Muratore, ). Other important characteristic of EVOO is the predominance of monounsaturated fatty acids over the unsaturated ones, hence the intake of EVOO presents positive results in the increase of HDL (High‐Density Lipoproteins) and reduction of LDL (Low‐Density Lipoproteins) oxidation (Piscopo & Poiana, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra‐virgin olive oil (EVOO) is obtained from olives solely by mechanical or other physical processes. The presence of natural antioxidant components such as carotenoids, chlorophylls, and tocopherol is a typical characteristic of EVOO, which is an advantage in comparison with other vegetable oils that have these components removed because of the refining process they are submitted (Rizzo, Torri, Licciardello, Piergiovanni, & Muratore, ). Other important characteristic of EVOO is the predominance of monounsaturated fatty acids over the unsaturated ones, hence the intake of EVOO presents positive results in the increase of HDL (High‐Density Lipoproteins) and reduction of LDL (Low‐Density Lipoproteins) oxidation (Piscopo & Poiana, ).…”
Section: Introductionmentioning
confidence: 99%
“…Materials which have been used for olive oil packaging, that are mainly sold in bottles, include glass, metals, and more recently plastics (Pristouri et al, ; Rizzo et al, ). In the past few years, there was an increased interest in developing environmentally friendly packaging, as those are biodegradable, are produced from renewable resources, and are an attractive alternative to substitute synthetic and nonbiodegradable plastics (Carpiné, Dagostin, Bertan, & Mafra, ; Iahnke, Costa, Rios, & Flores, ).…”
Section: Introductionmentioning
confidence: 99%
“…Light transmission reference (Tr) at 550 nm obtained for sample A and B was 87% and 86%, ie, higher than 85% and therefore attends the specification as transparent glass according to the National Standard . Rizzo also demonstrated that clear plastic bottle showed a light transmittance of 80% to 90% from 400 to 700 nm.…”
Section: Resultsmentioning
confidence: 91%
“…Rizzo demonstrated that the best light barrier property was for the white PET bottle (opaque plastic), but it still showed a light transmittance around 20% to 30% in the chlorophyll light absorption range (400‐500 nm and 600‐700 nm). Green, orange, and blue PET bottles showed a light transmittance around 50% to 80% in the same wavelength range . Although the colour may appear darker, it does not always have a sufficient light barrier to protect the product at a specific wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation